Relationship between Quantitative C-Reactive Protein (CRP) Levels and Leukocyte Counts in Pulmonary Tuberculosis Infection Patients at Arifin Achmad Regional Hospital - Telambanua, Arniat Christiani; Ressi Oktaviani; Adewirli Putra (Rajaki of Tulip Medika Publisher, 2024)
Pulmonary tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis. C-reactive protein (CRP) and leukocyte count are indicators that can reflect the severity of infection in pulmonary TB patients. This study aims to analyze the relationship between quantitative CRP levels and leukocyte counts in pulmonary tuberculosis patients. This study is an observational analytical study with a cross-sectional approach conducted on 30 pulmonary TB patients at Arifin Achmad Hospital, Pekanbaru who met the inclusion and exclusion criteria. Data on CRP levels and leukocyte counts were obtained through laboratory examinations, while demographic data were taken from patient medical records. Normality and linearity tests were performed before correlation analysis using linear regression tests. The average CRP level of patients was 84.14 ± 91.59 mg/L, with the lowest level of 0.71 mg/L and the highest of 316.7 mg/L. The mean number of leukocytes was 10,481 ± 4,625.53 mm³, with the lowest number of 3,190 mm³ and the highest of 21,310 mm³. The results of the bivariate analysis showed no significant relationship between CRP levels and leukocyte counts in pulmonary TB patients (p = 0.378). There was no significant correlation between quantitative CRP levels and leukocyte counts in pulmonary tuberculosis patients at Arifin Achmad Hospital Pekanbaru. Further research with larger samples and longitudinal designs is needed to further explore the relationship between these two variables and their implications in the management of pulmonary TB.